Potato Production in the Tropical Highlands: Constraints, Fungicide Use and The Impact of IPM Strategies - Olanya, O.M.; Hakiza, J.J.; Crissman, C.C. (Outlooks on Pest Management, 2004)
Potato (Solanum tuberosum) is an important cash and food crop in various tropical highlands of Africa, Asia and Latin America. Potato production in the tropical regions of the world is quite diverse involving ecological, cultural and economic considerations. The total production in the tropics is estimated at about 100 million metric tons and per capita consumption is about 20 kg/per person per year. In the tropical highland regions, ambient temperature conditions during the cropping season range from 14 to 25 C. The rainfall received during the cropping seasons is often adequate (> 1,200 mm/annum). Potato production (total acreage & yield) and consumption is increasing in the tropical highlands. The majority of potato production in the tropical regions of the world is however, found in the IndoGangetic plains and southern China where growing conditions, IPM techniques and other practices are very different from the tropical highlands of Africa and Latin America.
Keywords: Potato production; Tropical highlands; Fungicide